The Diagnostic Yield and Cost of Radiologic Imaging for Urgent and Emergent Ocular Conditions in an Eye Emergency Room - Deaner, Jordan D.; Meeker, Austin R.; Ozzello, Daniel J.; Swaminathan, Vishal; Amarasekera, Dilru C.; Zhang, Qiang; Hamershock, Rose A.; Sergott, Robert C. (Journal of Academic Ophthalmology, 2020)
Objective The aim of this study is to assess the diagnostic yield and economic cost of radiologic imaging for urgent and emergent ophthalmic conditions in an emergency room (ER) settingDesign Retrospective, consecutive case series.Methods Charts of all patients who underwent radiologic imaging in a dedicated eye ER over a single year were reviewed. Data collected included age, patient reported chief complaint, visual acuity, principal examination finding, indication for imaging, imaging modalities performed, and the current procedural terminology (CPT) codes billed for the imaging performed. Imaging results were classified into three groups with binary outcomes: normal or abnormal; significant if it led to a change in patient management, and relevant if the imaging findings were related to the chief complaint or principal examination finding. Imaging costs were calculated using the billed CPT codes.Results A total of 14,961 patients were evaluated during the 1-year study and 1,371 (9.2%) patients underwent imaging. Of these, 521 patients (38.0%) had significant findings. A majority of this group had significant and relevant findings (469, 34.2% of total). Subgroup analysis was performed based upon patient chief complaint, principal examination finding, and indication for imaging. Overall, the total cost of imaging was $656,078.34 with an average cost of $478.54 per patient.Conclusion Imaging for urgent and emergent ophthalmic conditions in an eye ER resulted in significant management changes in 38.0% of patients. Radiographic imaging contributes to healthcare expenditures; however, these costs must be weighed against the substantial costs of delayed and misdiagnoses, especially when patients present with acute ophthalmological symptoms.
Keywords: diagnostic yield; imaging; cost; economic; emergency room